Reporting Financial Performance : current developments and future directions - Johnson, L. Todd.; Lennard, Andrew (United Kingdom : Financial Accounting Standards Board, 1998)
This paper addresses, from a long-term perspective, some of the conceptual issues associated with performance reporting.
Includes bibliographical references.
osc 05/09/2016
Loans
Keywords: Financial Reporting